Pelatihan Pengolahan Keripik Singkong untuk Pemberdayaan Ekonomi Masyarakat Desa Jati - Hikmawati, Hanifah; Sulastri, Sulastri (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This training aims to empower the Jati Village community by increasing skills in processing cassava into cassava chips, with the hope of encouraging local economic growth and creating jobs. This training program includes theoretical and practical sessions on cassava processing techniques, product innovation, as well as marketing and business management strategies. The results of the training showed a significant increase in participants' skills, including the ability to select quality raw materials, processing and packaging of cassava chips. Participants reported increased income and success in starting new businesses, which have created additional jobs in the village. This training was successful in achieving the goals of economic empowerment and improving community welfare, however additional follow-up and support is needed to ensure long-term business sustainability and development.